2022
DOI: 10.1007/s10965-022-03019-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Cellulose Nanofibre Films at High Temperatures

Abstract: Nanocelluloses and their different designs, such as films and nanopapers, have gained considerable interest in many application areas due to their unique properties. For many purposes, such as packaging and electronics, the thermal stability and optical properties of nanocellulose materials are crucial characteristics. In this study, the effects of heat treatment (100 ºC, 150 ºC and 200 ºC) on the optical and mechanical properties of 2,2,6,6-tetramethylpiperidinyl-1-oxy radical-oxidised cellulose nanofibre (TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…43 For instance, it has been found that the RIs for cellulose and chitin are ∼1.54 and ∼1.56, respectively. 44,45 At a higher temperature, the RI for cellulose increases while that for chitin decreases, 46,47 so the RI difference between CNC and ChNW likely decreases with an increasing temperature, which may cause an decrease in haze. A decrease in transmittance at shorter wavelengths was especially pronounced for S100T40.…”
Section: Resultsmentioning
confidence: 99%
“…43 For instance, it has been found that the RIs for cellulose and chitin are ∼1.54 and ∼1.56, respectively. 44,45 At a higher temperature, the RI for cellulose increases while that for chitin decreases, 46,47 so the RI difference between CNC and ChNW likely decreases with an increasing temperature, which may cause an decrease in haze. A decrease in transmittance at shorter wavelengths was especially pronounced for S100T40.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the formation of hydrophilic groups caused by thermal degradation is also implied in the contact angle measurements, which showed a considerable decrease in films treated at 200 C (WCA of 35 ). A reduction in strength and strain was noticeable at higher temperatures (Niskanen et al 2022).…”
Section: Heat Treatmentmentioning
confidence: 94%